The Role of Popular Diplomacy In Managing International Crises (Russian Popular Diplomacy As A Model) (Al-Mostansiriyah journal for Arab and international studies, 2026)
The role of peoples in influencing political situations is something that has existed since ancient times, Popular diplomacy as a practice has been around for a long time, but its theoretical framing has not been completed until recently. The first form of popular diplomacy was embodied in cultural and media diplomacy, With the developments that occurred over time, other types emerged, such as sports diplomacy and digital diplomacy, which have a prominent and important role at the present time.Today, countries have been interested in employing popular diplomacy in parallel with their official diplomacy, realizing its importance in supporting their foreign policy and their relationship with the outside world. The most prominent country that employed it is Russia. Russia's communist history has left major impacts on Russia's image In front of the world. With the fall of communism, Russia needed this type of diplomacy on a large scale and still does, using this type of diplomacy as a means to fix what it cannot fix through its official diplomacy.